Staged vs Complete Repair in Tetralogy of Fallot With Pulmonary Atresia - Boucek, Katerina; Mastropietro, Christopher W.; Beall, Jonathan; Keller, Everette; Beshish, Asaad; Flores, Saul; Chlebowski, Meghan; Yates, Andrew R.; Choudhury, Tarif A.; Mueller, Dana; Kwiatkowski, David M.; Migally, Karl; et al. (The Annals of thoracic surgery, 2023)
We sought to compare outcomes for infants with tetralogy of Fallot with pulmonary atresia (TOF/PA) and confluent pulmonary arteries who underwent staged or primary complete surgical repair. This retrospective study included infants undergoing initial surgical intervention between 0 and 60 days of age with TOF/PA without aortopulmonary collaterals from 2009 to 2018 at 20 centers. The primary outcome was days alive and out of the hospital in the first year of life (DAOH365). Secondary outcomes were mortality at 1 year of age and a composite major complication outcome. Multivariable modeling with generalized estimating equations were used to compare outcomes between groups. Of 221 subjects, 142 underwent staged repair and 79 underwent primary complete repair. There was no significant difference in median DAOH365 between the staged and primary repair groups (317 days [interquartile range, 278-336] vs 338 days [interquartile range, 314-348], respectively; adjusted P = .13). Nine staged repair patients (7%) died in the first year of life vs 5 primary repair patients (6%; adjusted odds ratio, 1.00; 95% CI, 0.25-3.95). At least 1 major complication occurred in 37% of patients who underwent staged repair vs 41% of patients who underwent primary complete repair (P = .75), largely driven by the need for unplanned cardiac reinterventions. For infants with TOF/PA with confluent pulmonary arteries, a surgical strategy of staged or primary complete repair resulted in statistically similar DAOH365, early mortality, and morbidity.